2009
DOI: 10.1007/s12206-008-1002-8
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric hollow cylinder with thermal gradient

Abstract: The coupling nature of piezoelectric materials has acquired wide applications in electric-mechanical and electric devices. Recent advances in smart structures technology have led to a resurgence of interest in piezoelectricity, and in particular, in the solution of fundamental boundary value problems. In this paper, an analytic solution to the axisymmetric problem of a radially polarized, radially orthotropic piezoelectric hollow cylinder with thermal gradient is developed. An analytic solution to the governin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…As can be seen from Fig. 3, radial stresses are constant with respect to time at the interior and exterior surfaces of the cylinder, satisfying the constant Table 1 Mechanical, thermal and electrical properties of PZT_5 [5,11]. Table 2.…”
Section: Numerical Results and Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…As can be seen from Fig. 3, radial stresses are constant with respect to time at the interior and exterior surfaces of the cylinder, satisfying the constant Table 1 Mechanical, thermal and electrical properties of PZT_5 [5,11]. Table 2.…”
Section: Numerical Results and Discussionmentioning
confidence: 71%
“…Babaei and Chen [4] continued the work of Chen and Shi [3] and found that hoop stress does not decrease below a fixed amount irrespective of electric boundary conditions. However, Saadatfar and Razavi [5] analyzed the stresses in piezoelectric hollow cylinder with thermal gradient and demonstrated that the amount of hoop stress resulting from mechanical loads could be reduced by imposing a suitable electrical field. Khoshgoftar et al [6] worked on a combination of the above factors and studied thermopiezoelectric behavior of a thick-walled cylinder made of functionally graded piezoelectric materials under a thermal gradient as well as inner and outer pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that an existing mechanical hoop stress distribution could be neutralized by a suitably applied electric field. Saadatfar and Razavi analyzed the stress in piezoelectric hollow cylinder with thermal gradient. An analytic solution to the axisymmetric problem of an infinitely long, radially polarized, radially orthotropic piezoelectric hollow circular cylinder rotating about its axis at constant angular velocity was also developed by Galic and Horgan .…”
Section: Introductionmentioning
confidence: 99%
“…Piezoelectric materials are one of the smart materials currently being used in structures to control deformation, vibration, buckling, and so on (Behjat et al, 2009;Bhattacharya et al, 1998;Brischetto and Carrera, 2009;Ghorbanpour Arani et al, 2006;Komijani et al, 2013;Saadatfar and Rastgoo, 2008;Saadatfar and Razavi, 2009). In recent years, smart structures including functionally graded materials (FGMs) or multilayered composite members bonded with piezoelectric actuators and sensors are extensively investigated.…”
Section: Introductionmentioning
confidence: 99%